Dialectal Attitudes of Juozas Balčikonis: Dialectal and Figurative Lexicon in His Writings - Kruopienė, Irena; Kačiuškienė, Genovaitė (Acta humanitarica academiae Saulensis, 2025)
In 2025, the 140th anniversary of Juozas Balčikonis is being commemorated – a historian of language, dialectologist, grammar specialist, toponymist, folklorist, promoter of linguistic purity, and lexicographer. Juozas Balčikonis was born in Panevėžys region, which belongs to the expansive and vibrant Eastern Aukštaitian (Panevėžys) subdialect. He repeatedly expressed – both directly and indirectly – a positive attitude toward dialects, concern for their future, and emphasized the significance of dialectal forms for linguistic science. Numerous such remarks can be found throughout his published works dealing with language issues. This article discusses Balčikonis’s dialectal views and examines dialectal vocabulary, vivid words, and expressions that appear in his writings. The analysis draws on examples from the two-volume Collected Works (Rinktiniai raštai), published in 1978 and 1982 (compiled by Aldonas Pupkis), the memoir book Add Word to Word – You’ll Have a Dictionary (Dėk žodį prie žodžio – turėsi žodyną), compiled by Birutė Goberienė and Aldonas Pupkis (2006), as well as on various folktale translations carried out by the linguist himself. The study shows that Balčikonis most often addressed the importance of dialects in articles written for the Dictionary of the Lithuanian Language, and he frequently treated the linguistic features – lexical or grammatical – of his native dialect as benchmarks, viewing them as unquestionable when proposing or validating certain grammatical forms or toponymic equivalents in the standard Lithuanian language. Moreover, Balčikonis made abundant use of dialectal features and vivid lexicon in his own work – both in folktale translations and non-fictional texts.